Synthesis of C-5a-chain extended derivatives of 4-epi-isofagomine: Powerful β-galactosidase inhibitors and low concentration activators of GM1-gangliosidosis-related human lysosomal β-galactosidase. Issue 5 (1st March 2016) - Thonhofer, Martin; Weber, Patrick; Santana, Andres Gonzalez; Fischer, Roland; Pabst, Bettina M.; Paschke, Eduard; Schalli, Michael; Stütz, Arnold E.; Tschernutter, Marion; Windischhofer, Werner; Withers, Stephen G.
Graphical abstract: Abstract: From an easily available partially protected formal derivative of 1-deoxymannojirimycin, by hydroxymethyl chain-branching and further elaboration, lipophilic analogs of the powerful β-d -galactosidase inhibitor 4- epi -isofagomine have become available. New compounds exhibit improved inhibitory activities comparable to benchmark compound NOEV ( N -octyl- epi -valienamine) and may serve as leads towards improved and more selective pharmacological chaperones for GM1 -gangliosidosis.